Preoperative versus Post-operative Radiotherapy for Extremity Soft tissue Sarcoma: a Systematic Review and Meta-analysis of Long-term Survival. Issue 10 (October 2021) - Kungwengwe, Garikai; Clancy, Rachel; Vass, Johanne; Slade, Robert; Sandhar, Simarjit; Dobbs, Thomas D.; Bragg, Thomas W.H.
Summary: Background: The role of perioperative radiotherapy in the management of resectable extremity soft tissue sarcoma (ESTS) is widely recognised for local tumour control, wound complications (WC) and long-term function. However, debate continues regarding its implications on long-term survival. This study aimed to determine whether the timing of perioperative radiotherapy affects long-term survival outcomes in adults with ESTS. Methods: A systematic literature search of MEDLINE, EMBASE, Web of Science and Cochrane was performed. The primary outcome measure was the pooled hazard ratio (HR) at 95% confidence intervals. Secondary outcomes and subgroup analyses were presented as cumulative odds ratios (OR). A random-effects, generic inverse variance method and sensitivity analysis were performed to minimise heterogeneity. Results: Six studies ( n = 4192 patients) were identified. Time-to-event analysis demonstrated a statistically significant advantage in post-operative radiotherapy for overall survival (HR 1.15 and p = 0.05). Combined HRs for disease-free (1.25 and p = 0.22) and disease-specific (1.06 and p = 0.43) survival also favoured post-operative radiotherapy but did not achieve statistical significance. Post-operative radiotherapy was shown to confer an overall (OR 1.19 and p = 0.01), disease-free (OR 1.19 and p = 0.01) and disease-specific (OR 1.19 and p = 0.01) survival advantage on subgroup analysis. This survival benefit was best observed at three years in the disease-free survival comparison (OR 1.55 and p = 0.003). Preoperative radiotherapy was associated with more WC (OR 2.74 and p<0.00001). Conclusions: Pooled analysis of published literature suggests that post-operative radiotherapy confers a significant long-term survival advantage with fewer WC. Further large multicentre randomised controlled trials with long-term follow-up are required to determine the optimal perioperative radiotherapy regime in adult ESTS.